Preliminary investigation on combustion characteristics of rice husk in FBC - Permchart, W.; Tanatvanit, S. (My University, 2009)
The experimental results on combustion of rice husk in a conical fluidized bed combustor (referred to as the conical FBC) using silica sand as the bed material are presented in this paper. The effects of excess combustion air and combustor loading as well as the sand bed height on the combustion pattern in FBC were investigated. Temperatures and gas concentrations (CO and NO) along over the combustor height as well as in the flue gas downstream from the ash collecting cyclone were measured. The results showed that the axial temperature profiles in FBC were explicitly affected by the combustor loading whereas the excess air and bed height were found to have minor influences on the temperature pattern. Meanwhile, the combustor loading and the excess air significantly affected the axial CO and NO concentration profiles; however, these profiles were almost independent of the bed height. The combustion and thermal efficiencies for this FBC were quantified for different operating conditions.
Keywords: Bed height; Combustor loading; Excess air; Temperature